IDENTIFICATION OF CYTOTOXIC AND ANTIOXIDANT COMPOUNDS FROM ALLIUM GRAMINEUM FLOWERS (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The present study evaluates the in vitro anticancer, antiplasmodial and antioxidant activity of the ethanolic crude extract from the flowers of Allium gramineum growing in Georgia and of one flavonol and two steroidal glycosides which were isolated from this plant. The flowers were extracted with ethanol and this total extract was subjected to successive bioguided fractionations to provide glycosides 1-3. Their structures were elucidated on the basis of NMR and ESI-MS spectrometric data in comparison with the existing literature and have been identified as: isorhamnetin-3-O-β-D-glucopyranoside (1), diosgenin-3-O-α-rhamnopyranosyl-(1→2)-β-D-glucopyranoside (Prosapogenin A of dioscin) (2), diosgenin-3-O-α-rhamnopyranosyl-(1→2)-[β-D-glucopyranosyl-(1→4)-]-β-D-glucopyranoside (Deltonine) (3). The ethanolic extract has been shown to strongly inhibit the growth of breast adenocarcinoma cell lines, with an IC50 of 4.5 ± 0.7μg/mL for MDAMB-231 and 4.8 ± 0.9μg/mL for MCF-7 cells. The cytotoxic activity was related to 2 and 3 which exhibited potent cytotoxicity, with an IC50 of ± 3μM. Concerning antiplasmodial activities, only weak activities were observed using the ethanolic extract and the two saponins. The flavonoid was almost inactive. Finally, the radical-scavenging activity of the ethanolic extract was tested in presence of ABTS•+ solution. A decrease of the absorbance intensity was observed, with an IC50 value of 22.1 ± 0.6μg/mLwhile trolox, used as Standard drug, showed a pronounced activity (IC50 = 12.7±0.5μM). The glycoside 1 showed the lowest IC50 value of 20.1 ± 0.8μM while both 2 and 3 exhibited very weak radical scavenging activity.